Ideal, expected and perceived descriptive norm drunkenness in UK nightlife environments: a cross-sectional study - Karen Hughes; Zara Quigg; Kat Ford; Mark A. Bellis (BMC, 2019)
Abstract Background Drunkenness is common in nightlife environments and studies suggest it can be considered both desirable and normal by nightlife users. We aimed to compare UK nightlife users' ideal levels of drunkenness to their expected drunkenness on a night out and their perceptions of descriptive nightlife norms. Methods A cross-sectional survey with nightlife patrons (n = 408, aged 18-35) in three cities. Using a scale from 1 (completely sober) to 10 (very drunk), participants rated: personal drunkenness at survey; expected drunkenness on leaving nightlife; perceived descriptive drunkenness norm in the city's nightlife; and ideal personal drunkenness. Analyses were limited to those who had or were intending to consume alcohol. Results Almost half of participants (46.8%) expected to get drunker than their reported ideal level on the night of survey, rising to four fifths of those with the highest levels of expected drunkenness. 77.9% rated typical nightlife drunkenness ≥8 but only 40.9% expected to reach this level themselves and only 23.1% reported their ideal drunkenness as ≥8. Higher expected drunkenness was associated with higher ideal drunkenness, higher perceived drunkenness norm and later expected home time. Conclusions Nightlife users' perceptions of typical drunkenness in nightlife settings may be elevated and many of the heaviest drinkers are likely to drink beyond their ideal level of drunkenness. Findings can support emerging work to address cultures of intoxication in nightlife environments and suggest that interventions to correct misperceptions of normal levels of nightlife drunkenness may be of benefit.